The Determinants of Level of Society Welfare Within Fiscal Decentralization Framework In Regional Autonomy Era - Priyono, Nuwun; Arifah, Siti; Wulandari, Eva; Prasetyanto, Panji Kusuma (Muhammadiyah University Press, 2020)
The purpose of this study is to prove to what extent the influence that fiscal decentralization, local financial performance, local government expenditure, Locally Generated Recurring Revenues or Pendapatan Asli Daerah (PAD), Profit-Sharing Fund or Dana Bagi Hasil (DBH), General Allocation Fund or Dana Alokasi Umum (DAU), and Special Allocation Fund or Dana Alokasi Khusus (DAK) have on the level of society welfare. The objects of this research are Regencies and Municipalities in Java Island. The data used in this study are the secondary. The data on balance sheet and realization report of the regional revenues and expenditure budget (APBD) are from the Ministry of Finance of the Republic of Indonesia. The data on the level of society welfare that is proxyed by the value of HDI is obtained from Bappenas and BPS of Central Java. This research uses time series data from 2012-2014 periods. The research method used is the research of causality with linear regression model. The result of the significance test shows that only one DAK variable can partially affect the HDI variable. Meanwhile those variables other than DAK partially or individually do not influence the HDI variable. The result of regression analysis shows that simultaneously such variables as Fiscal Decentralization, Regional Finance Performance, Local Government Expenditure, PAD, DAU, DAK and DBH have an influence on HDI in Regencies / Municipalities in Java Island.